Systematic revision of the Andean butterfly genus Orophila Staudinger, 1886 (Lepidoptera: Nymphalidae: Biblidinae) - Zubek, Anna; Pyrcz, Tomasz; Lorenc-Brudecka, Jadwiga; Boyer, Pierre; Cerdeña, Jose; Mahecha-Jiménez, Oscar; Huertas, Blanca (Zootaxa, 2017)
A systematic review of the Neotropical butterfly genus Orophila Staudinger, 1886 based on morphological characters and geographical distribution is presented. Four species are recognized: O. campaspe (Hewitson, 1869) stat. rest., O. cardases (Hewitson, 1869), O. cecidas (Hewitson, 1869) stat. rest. and O. diotima (Hewitson, 1852). Other changes proposed include treating Orophila diotima footei (Lamas, 2003) syn. n. and O. cardases zurita (Fruhstorfer, 1916) syn. n. as synonyms of other taxa. Illustrations of adult males and male genitalia of all taxa are presented and the importance of morphological characters in both males and females is evaluated. Female specimens and genitalia are illustrated for the first time for O. c. cardases, O. cecidas and O. diotima. Lectotypes are designated for two nominal taxa.